Effect of Health Promotion Using Leaflets on Childbirth Readiness in Pregnant Women - Cholijah Oktapia Pia; Jenny Anna Siauta; Suprihatin (KHD Production, 2024)
The prevalence of pregnant women with K4 coverage at the Cilincing Community Health Center in 2022 remains up to the target. There are still pregnant women who do not have an immature birth plan, so they still choose to give birth to a non-health worker. This study aims to determine the effect of health promotion using leaflets on childbirth readiness in pregnant women. This quasi-experiment research uses a pre and post-test design. The sample in this study amounted to 31 people. The sampling technique uses purposive sampling. The research instrument consists of a questionnaire regarding childbirth readiness, tested for validity and reliability using Cronbach's alpha coefficient of 0.876. Data were analyzed using descriptive statistics and paired sample T-Test to determine the effect of health promotion using leaflets on childbirth readiness. The research results show an influence of health promotion using leaflets on pregnant women's readiness to give birth, with a p-value of 0.000 (p<0.05). Health promotion using leaflets increases childbirth readiness in pregnant women. It is hoped that this research can provide additional insight for readers, especially prospective midwives, so they can later apply it when providing midwifery care services to pregnant women.